Pengaruh Motivasi Belajar terhadap Hasil Belajar Kognitif Sejarah Siswa Fase E SMA Negeri 12 Padang - Fismariza, Wiwi; Karima, Elfa Michellia (MASALIQ, 2024)
History learning is a branch of science that discusses the origin, development, and role of society in the past that bears the value of wisdom that is useful in shaping the attitudes and personality of students. The purpose of this study was to analyze how learning motivation significantly affects the cognitive learning outcomes of Phase E students of SMA Negeri 12 Padang. This type of research is quantitative research. This research is descriptive with an inductive approach. The method used in this research is regression analysis conducted at SMA Negeri 12 Padang. Based on the results of research and discussion that researchers have done related to the influence of learning motivation on cognitive learning outcomes of history phase E students of SMA Negeri 12 Padang, it can be concluded that there is a positive and significant influence between learning motivation on learning outcomes.